Annie knows everything : a novel - Wood, Rachel (The Dial Press, 2026)
"After getting let go from her job and learning her sister is engaged to the worst man alive, Annie needs a win. Filling the open role in her company's data strategy team is just what the doctor ordered. So what if she doesn't know how to write code? How hard can it be? Surely Connor--the team's overworked, aggravating, and distractingly hot interim head--will soon realize how capable Annie is. Annie sets her sights on landing this new job, even if that means ignoring the chemistry building between her and her new boss, and she tries to (gently!) convince her sister to reconsider her engagement. But with sparks flying at work and at home, she begins to see how complicated taking matters into her own hands can be. Maybe, just maybe, Annie doesn't actually know everything."--